STUDENTS’ MASTERY IN SUBJECT-VERB AGREEMENT - J Sutomo (Dinamika Bahasa dan Budaya, 2011)
The aim of the research was to identify the subject-verb agreement errors in the students’ descriptive writings. This study discussed the reasons for the productions of subject-verb agreement errors in students’ writings. A total of 25 writings were collected from the second semester students of Faculty of Language and Cultural Studies of University of Stikubank Semarang in the academic year 2009-2010. The average number of clauses of each writing was 40. The researchers took 20 clauses (50%) from each writing as samples, so there were 500 clauses to be analyzed. The frequency of errors was identified through the analysis of the students’ descriptive writing. The findings of the study showed that there were 124 errors (24.80%) in subject-verb agreement produced by the students in their descriptive writings. From the findings of the study, the researchers summarized that the errors produced by the students were due to the L1 (Indonesian language) interference whereby the students transferred and translated their L1 into L2 (English language).  Other reason for the error production was errors whereby the students could not apply the rule of the subject-verb agreement appropriately in their writings. The results of the study showed that the students still need more instruction and practice in using subject-verb agreement in their writings. Keywords: descriptive writing, subject-verb agreement, clauses